Causes and Incidence of Early Repolarization and its Alteration in Electrocardiogram in Patients with Chest Pain - Ahmad, Iftikhar; Malik, Shakoor Ahmad; Ahmad, Munir; Mustafa, Zia Ul; Uddin, Muhammad Aleem; Adil, Muhammad (Journal of Neonatal Surgery, 2025)
Background: The “early repolarization (ER)” pattern, previously regarded as benign, has recently shown associations with adverse outcomes, including all-cause, arrhythmic and cardiac mortality. Objective: This study set out to determine how often chest pain is at a tertiary cardiac center and what variables are associated with electrocardiogram (ECG) abnormalities in the emergency room. Methods:A total of 160 individuals ranging in age from 20 to 78 years old who reported chest pain were included in this descriptive cross-sectional research. Detailed demographic information was obtained after obtaining informed written consent. In order to evaluate the ER pattern, baseline 12-lead electrocardiograms were utilized. All data was analyzed using SPSS 22.0. Results:The patients mean age was 58.7±11.65 years. There were majority 96 (60%) males and 64 (40%) females among all cases.Early repolarization pattern (ER) was present in 59 (36.9%). Hypertension, diabetes mellitus, obesity, family history of CAD and smoking were the comorbidities among all cases. Frequency of STEMI was found in 32 (20%) cases.Specific characteristics, such as a low body mass index (p<0.002), reduced T-wave length (p=0.002), and lower heart rate (p=0.003), were shown to be substantially linked with the ER patterns. Conclusion:Based on our findings, one-third of individuals experiencing chest discomfort have an ECG rhythm known as early repolarization. It is less common in individuals with STEMI and non-STEMI, and associated characteristics include a low body mass index (BMI), shorter T-wave length, and lower heart rate.